Price-settings and Price Dispersion in the Dutch Mortgage Market - Wolter H.J. Hassink; Michiel van Leuvensteijn (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2003)
We analyse empirically price-setting in the Dutch mortgage market, using information on about 124,000 Dutch households and 54 mortgage lenders over the years 1996-2001. For a narrowly defined set of mortgages (which have a fixed lending rate for ten years), the range of the lending rate between lenders varies between 0.86 and 1.24 percentage points over these years. Prices remain dispersed across lenders, even after controlling for the characteristics of the household and the municipality (1 percentage point). We find that the price dispersion of mortgages sold by banks is smaller than that of mortgages sold by life insurers (0.60 versus 1.28 percentage points). This difference may be due to lower agency costs for banks than for life insurers. Another likely explanation is that the market segment for banks is more transparent than that of insurance companies. This may imply that there is imperfect competition among lenders, so that some of them can develop market power. Furthermore, we find indications for market power since lenders with higher costs have higher lending rates, accounting for a maximum change of the lending rate by 0.076 – 0.16 percentage point.
Keywords: 330; Mortgage market; Price dispersion; Agency costs; Search costs; Lender-borrower matched data